2013
DOI: 10.1214/13-ba815
|View full text |Cite
|
Sign up to set email alerts
|

Simple Marginally Noninformative Prior Distributions for Covariance Matrices

Abstract: A family of prior distributions for covariance matrices is studied. Members of the family possess the attractive property of all standard deviation and correlation parameters being marginally noninformative for particular hyperparameter choices. Moreover, the family is quite simple and, for approximate Bayesian inference techniques such as Markov chain Monte Carlo and mean field variational Bayes, has tractability on par with the Inverse-Wishart conjugate family of prior distributions. A simulation study shows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
238
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(254 citation statements)
references
References 8 publications
0
238
0
Order By: Relevance
“…We set λ = 10, and local changes make little difference in terms of the Monte Carlo experiment below, Root Mean Squared Error (RMSE), or generalized impulse responses. Huang and Wand (2013) propose a prior for large sparse positive definite matrices where control is allowed over the standard deviations and the correlation coefficients. We use this in our study and provide more details on the Huang and Wand (2013) prior in Appendix 1.…”
Section: Priorsmentioning
confidence: 99%
“…We set λ = 10, and local changes make little difference in terms of the Monte Carlo experiment below, Root Mean Squared Error (RMSE), or generalized impulse responses. Huang and Wand (2013) propose a prior for large sparse positive definite matrices where control is allowed over the standard deviations and the correlation coefficients. We use this in our study and provide more details on the Huang and Wand (2013) prior in Appendix 1.…”
Section: Priorsmentioning
confidence: 99%
“…Recently, Huang et al (2013) proposed a hierarchical approach for the covariance matrix as shown in equation (4).…”
Section: Hierarchical Half-t Priormentioning
confidence: 99%
“…Alternative covariance matrix priors have been proposed including the scaled inverse Wishart (O'Malley and Zaslavsky 2005), a hierarchial inverse Wishart (Huang et al 2013), and a separation strategy (Barnard et al 2000). However Tokuda et al (2011) states that Even fewer analytical results are known for these families, making it even more challenging to understand precisely the properties of such distributions.…”
Section: Introductionmentioning
confidence: 99%
“…Refs. [12][13][14]. The covariance matrix M, and thus the likelihood, are then functions of ν, so that L(x|y, ν).…”
Section: Uncertainties On the Correlationmentioning
confidence: 99%